Battery for flooded parking air conditioner and manufacturing method thereof
By adding specific components to the lead paste formula of the battery and adding N-alkyl indoline additives to the electrolyte, the problems of conventional batteries being prone to power loss, vulcanization, and lead paste falling off are solved, and a battery with high deep cycle durability and service life is achieved.
Patent Information
- Application Number
- CN202411664126.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-04-04
AI Technical Summary
Conventional startup batteries in the prior art are prone to cause long-term power loss, vulcanization, and lead paste fall off, resulting in a short service life.
The liquid-rich parking air conditioning battery is used to improve the conductivity and binding force of the lead paste by adding specific components, such as stannous sulfate, antimony trioxide, graphite and high specific surface area carbon black, to the lead paste formula of the positive electrode and negative electrode plates; at the same time, N-alkyl indoline additives are added to the electrolyte to improve the corrosion layer structure of the positive electrode grid.
It effectively improves the deep cycle durability and service life of the battery, reduces the risk of lead paste falling off, and meets the requirements of high discharge depth.
Smart Images

Figure CN119764603A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lead-acid batteries, and in particular relates to a battery for a flooded parking air conditioner. The present invention also relates to a method for manufacturing the battery for a flooded parking air conditioner. Background Art
[0002] The battery is an important part of the car, and its main function is to provide electric energy for starting, ignition and lighting of the vehicle. In recent years, with the development and progress of society and the continuous pursuit of quality of life, the automotive industry, especially commercial vehicles, has installed on-board air conditioners, inverters, water heaters, induction cookers, electric blankets and other electrical appliances to improve the working comfort of drivers and passengers.
[0003] However, when this type of vehicle stops running, the engine needs to generate electricity to drive the on-board electrical appliances. This process consumes a lot of fuel, has high operating costs, and has large carbon emissions. In order to change this situation, mainstream manufacturers have designed DC-driven parking air conditioners on cars. When the vehicle stops running, the engine is turned off and the parking air conditioner is powered by the on-board starting battery. Since the discharge depth of the battery in this mode is required to be above 50%, and the discharge depth of conventional starting batteries is designed to be below 10%, conventional starting batteries are no longer able to meet this use requirement. If conventional starting batteries are used, it is easy to cause long-term battery power loss, sulfation, lead paste shedding and other undesirable phenomena, which ultimately leads to a shorter battery life and increased replacement frequency, causing great inconvenience for vehicle use. Summary of the invention
[0004] The first purpose of the present invention is to provide a battery for a flooded parking air conditioner, which solves the problem in the prior art that conventional starting batteries are prone to long-term battery loss, sulfation, lead paste shedding and other undesirable phenomena, resulting in a short battery life.
[0005] A second object of the present invention is to provide a method for manufacturing a battery for a flooded parking air conditioner.
[0006] The first technical solution adopted by the present invention is a battery for a flooded parking air conditioner, comprising a positive plate, a negative plate, a separator, an electrolyte and a battery tank.
[0007] The electrolyte is composed of the following components by mass percentage: 0.3% to 0.6% of N-alkyl indoline additives, 0.2% to 0.5% of fumed silica, 0.3% to 0.5% of anhydrous sodium sulfate, 35% to 38% of sulfuric acid, and the rest is deionized water, and the sum of the mass percentages of the components is 100%; The N-alkyl indoline additive is any one of an N-alkyl isoindoline derivative and an N-alkyl indoline derivative.
[0008] The first technical solution of the present invention is also characterized in that: The positive plate includes a positive grid, on which a positive lead paste is coated, the positive grid is a first lead-calcium-tin-aluminum alloy, and the first lead-calcium-tin-aluminum alloy is composed of the following components by mass percentage: 0.04% to 0.08% calcium, 1.0% to 1.5% tin, 0.008% to 0.016% aluminum, and the rest is lead, and the sum of the mass percentages of the components is 100%; The positive electrode lead paste is composed of the following components by mass percentage: lead powder 82%~83%, polyester staple fiber 0.06%~0.10%, stannous sulfate 0.05%~0.25%, antimony trioxide 0.05%~0.25%, graphite 0.10%~0.30%, sulfuric acid aqueous solution with a density of 1.4g / ml 6.5%~7.5%, and the rest is deionized water. The sum of the mass percentages of each component is 100%.
[0009] The negative plate includes a negative grid, on which negative lead paste is coated, the negative grid is a second lead-calcium-tin-aluminum alloy, and the second lead-calcium-tin-aluminum alloy is composed of the following components by mass percentage: 0.10% to 0.12% calcium, 0.1% to 0.4% tin, 0.008% to 0.016% aluminum, and the rest is lead, and the sum of the mass percentages of the components is 100%; The negative electrode lead paste is composed of the following components by mass percentage: lead powder 85%~87%, polyester staple fiber 0.06%~0.10%, sodium lignin sulfonate 0.15%~0.25%, ordinary carbon black 0.2%~0.3%, high specific surface area carbon black 0.20%~0.50%, barium sulfate 0.5%~0.7%, vanillin 0.15%~0.25%, sulfuric acid aqueous solution with a density of 1.4g / ml 5.5%~6.5%, and the rest is deionized water. The sum of the mass percentages of each component is 100%.
[0010] The specific surface area of ordinary carbon black is 20 / g~30 / g, the specific surface area of high specific surface area carbon black is 120 / g~180 / g.
[0011] Lead powder is made of electrolytic lead, and is composed of the following components by mass percentage: PbO is 70%~80%, Bi is 0.0002%~0.0006%, Fe is 0.002%~0.005%, Ag is 0.0002%~0.0005%, and the rest is Pb, and the sum of the mass percentages of each component is 100%.
[0012] The chemical formula of N-alkyl isoindoline derivatives is:
[0013] in: Represents hydrogen, ~ alkyl, represent ~ alkyl, Represents hydrogen, ~ alkyl.
[0014] The chemical structural formula of N-alkyl indoline derivatives is as follows:
[0015] in: Represents hydrogen, ~ alkyl, Represents hydrogen, ~ alkyl, represent ~ alkyl.
[0016] The second technical solution adopted by the present invention is a method for manufacturing a battery for a flooded parking air conditioner, and the specific steps are as follows: Step 1, preparing electrolyte for forming a battery for a flooded parking air conditioner; Step 2: inject the electrolyte used for formation in step 1 into a battery assembled with a positive plate, a negative plate, a separator, and a battery tank, and use a staged constant current formation for 23h to 27h. After the formation is completed, the electrolyte The mass percentage reaches 35%~38%.
[0017] The second technical solution of the present invention is also characterized in that: the specific steps of configuring the electrolyte for forming the battery for the flooded parking air conditioner in step 1 are as follows: Step 1.1, weighing by mass percentage: 0.3%-0.6% of N-alkyl indoline additive, 0.2%-0.5% of fumed silica, 0.3%-0.5% of anhydrous sodium sulfate, 35%-38% of sulfuric acid, and the rest of deionized water, the sum of the mass percentages of each component is 100%; the N-alkyl indoline additive is any one of N-alkyl isoindoline derivatives and N-alkyl indoline derivatives; Step 1.2, firstly prepare a sulfuric acid aqueous solution by using the sulfuric acid and deionized water weighed in step 1.1; then add the N-alkyl indoline additive, fumed silica, and anhydrous sodium sulfate weighed in step 1.1 to the sulfuric acid aqueous solution, and continuously disperse for 15 min to 20 min using a stirrer with a rotation speed of 2700 to 3100 rpm to obtain a sulfuric acid dispersion; Step 1.3, adjusting the mass percentage of H2SO4 in the sulfuric acid dispersion obtained in step 1.2 to 26.0% to 29.0% with deionized water to obtain a battery formation electrolyte for a flooded parking air conditioner.
[0018] Beneficial effects of the present invention: In the battery for the flooded parking air conditioner of the present invention, stannous sulfate, antimony trioxide and graphite added to the positive electrode lead paste formula increase the conductivity of the lead paste of the positive electrode active material at the end of discharge, while reducing the risk of the lead paste falling off; the carbon black with a high specific surface area added to the negative electrode lead paste formula inhibits the occurrence of the negative electrode power-deficient sulfidation phenomenon, and the addition of vanillin prevents water loss in the battery, thereby effectively increasing the service life of the battery.
[0019] The present invention discloses a method for manufacturing a battery for a flooded parking air conditioner. The battery for a flooded parking air conditioner manufactured by the method has large capacity and starting ability, deep cycle endurance and long service life. N-alkyl indoline additives are added to the electrolyte to improve the corrosion layer structure on the surface of the positive electrode grid, delay the corrosion of the positive electrode grid, and effectively increase the service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a comparison chart of the constant capacity discharge cycle endurance test results of Comparative Example 1 of the present invention; Figure 2 It is a comparison chart of the full-capacity discharge cycle endurance test results of Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0021] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0022] The first technical solution of the present invention is a flooded parking air conditioner battery, comprising a positive plate, a negative plate, a separator, an electrolyte and a battery tank. The flooded parking air conditioner battery is used as a starting battery, has a high discharge depth, can meet the discharge depth requirement of the starting battery, and has a long service life. It effectively solves the problem that conventional starting batteries are prone to long-term battery power loss, sulfation, lead paste shedding and other undesirable phenomena, resulting in a short battery service life.
[0023] The positive plate includes a positive grid, on which a positive lead paste is coated, which is solidified and dried to form a positive active material, the positive grid is a first lead-calcium-tin-aluminum alloy, and the first lead-calcium-tin-aluminum alloy is composed of the following components by mass percentage: 0.04% to 0.08% calcium, 1.0% to 1.5% tin, 0.008% to 0.016% aluminum, and the rest is lead, and the sum of the mass percentages of the components is 100%; The positive lead paste is composed of the following components by mass percentage: 82%~83% lead powder, 0.06%~0.10% polyester staple fiber, 0.05%~0.25% stannous sulfate, 0.05%~0.25% antimony trioxide, 0.10%~0.30% graphite, 6.5%~7.5% sulfuric acid aqueous solution with a density of 1.4g / ml, and the rest is deionized water. The sum of the mass percentages of each component is 100%. Among them, stannous sulfate, antimony trioxide, and graphite added to the positive lead paste formula increase the conductivity of the positive active material at the end of discharge, improve the bonding strength between the positive active material and the positive grid, and the utilization rate of the active material, while reducing the risk of the lead paste falling off.
[0024] The negative plate includes a negative grid, on which negative lead paste is coated, and after solidification and drying, negative active material is formed, the negative grid is a second lead-calcium-tin-aluminum alloy, and the second lead-calcium-tin-aluminum alloy is composed of the following components by mass percentage: 0.10% to 0.12% calcium, 0.1% to 0.4% tin, 0.008% to 0.016% aluminum, and the rest is lead, and the sum of the mass percentages of the various components is 100%; The negative lead paste is composed of the following components by mass percentage: 85% to 87% lead powder, 0.06% to 0.10% polyester staple fiber, 0.15% to 0.25% sodium lignin sulfonate, 0.2% to 0.3% ordinary carbon black, 0.20% to 0.50% high specific surface area carbon black, 0.5% to 0.7% barium sulfate, 0.15% to 0.25% vanillin, 5.5% to 6.5% sulfuric acid aqueous solution with a density of 1.4g / ml, and the rest is deionized water, and the sum of the mass percentages of each component is 100%. Among them, the high specific surface area carbon black added to the negative lead paste formula reduces the volume of lead sulfate crystals formed during the discharge process of the negative active material, improves the recharge performance of the battery, and also inhibits the occurrence of negative electrode sulfidation; vanillin prevents the deposition of antimony ions on the negative active material, reduces the water loss of the battery, and effectively increases the service life of the battery.
[0025] The specific surface area of ordinary carbon black is 20 / g~30 / g, the specific surface area of high specific surface area carbon black is 120 / g~180 / g.
[0026] Lead powder is made of electrolytic lead, and is composed of the following components by mass percentage: PbO is 70%~80%, Bi is 0.0002%~0.0006%, Fe is 0.002%~0.005%, Ag is 0.0002%~0.0005%, and the rest is Pb, and the sum of the mass percentages of each component is 100%.
[0027] The electrolyte is composed of the following components by mass percentage: 0.3% to 0.6% of N-alkyl indoline additives, 0.2% to 0.5% of fumed silica, 0.3% to 0.5% of anhydrous sodium sulfate, 35% to 38% of sulfuric acid, and the rest is deionized water, and the sum of the mass percentages of the components is 100%; The N-alkyl indoline additive is composed of any one of N-alkyl isoindoline derivatives and N-alkyl indoline derivatives. Among them, the N-alkyl isoindoline derivatives or N-alkyl indoline derivatives added to the electrolyte improve the corrosion layer structure on the surface of the positive electrode grid, delay the corrosion of the positive electrode grid, and increase the service life of the battery.
[0028] The chemical formula of N-alkyl isoindoline derivatives is:
[0029] in: Represents hydrogen, ~ alkyl, represent ~ alkyl, Represents hydrogen, ~ alkyl.
[0030] The chemical structural formula of N-alkyl indoline derivatives is as follows:
[0031] in: Represents hydrogen, ~ alkyl, Represents hydrogen, ~ alkyl, represent ~ alkyl.
[0032] The second technical solution of the present invention is a method for manufacturing a battery for a flooded parking air conditioner, and the specific steps are as follows: Step 1: Prepare the electrolyte for forming the battery for the flooded parking air conditioner. The specific steps are as follows: Step 1.1, weighing by mass percentage: 0.3%-0.6% of N-alkyl indoline additive, 0.2%-0.5% of fumed silica, 0.3%-0.5% of anhydrous sodium sulfate, 35%-38% of sulfuric acid, and the rest of deionized water, the sum of the mass percentages of each component is 100%; the N-alkyl indoline additive is any one of N-alkyl isoindoline derivatives and N-alkyl indoline derivatives; Step 1.2, firstly prepare a sulfuric acid aqueous solution by using the sulfuric acid and deionized water weighed in step 1.1; then add the N-alkyl indoline additive, fumed silica, and anhydrous sodium sulfate weighed in step 1.1 to the sulfuric acid aqueous solution, and continuously disperse for 15 min to 20 min using a stirrer with a rotation speed of 2700 to 3100 rpm to obtain a sulfuric acid dispersion; Step 1.3: Add deionized water to the sulfuric acid dispersion obtained in step 1.2. The mass percentage of is adjusted to 26.0% to 29.0% to obtain a battery formation electrolyte for a flooded parking air conditioner.
[0033] Step 2: inject the electrolyte of step 1 into the battery assembled with positive plate, negative plate, separator and battery tank, and use staged constant current formation for 23h to 27h. The mass percentage reaches 35.0%~38.0%.
[0034] The battery for flooded parking air conditioner manufactured by the above method has large capacity and starting ability, and long deep cycle endurance and service life; the N-alkyl isoindoline derivative or N-alkyl indoline derivative added to the electrolyte improves the corrosion layer structure on the surface of the positive electrode grid, delays the corrosion of the positive electrode grid, and increases the service life of the battery.
[0035] The present invention provides a battery for a flooded parking air conditioner, and the specific embodiments are as follows: Example 1 The battery for the flooded parking air conditioner of the present invention comprises a positive plate, a negative plate, a separator, an electrolyte and a battery tank; The electrolyte is composed of the following components by mass percentage: 0.3% to 0.6% of N-alkyl indoline additives, 0.2% to 0.5% of fumed silica, 0.3% to 0.5% of anhydrous sodium sulfate, 35% to 38% of sulfuric acid, and the rest is deionized water, and the sum of the mass percentages of the components is 100%; The N-alkyl indoline additive is any one of an N-alkyl isoindoline derivative and an N-alkyl indoline derivative.
[0036] Example 2 The battery for the flooded parking air conditioner of the present invention comprises a positive plate, a negative plate, a separator, an electrolyte and a battery tank; The electrolyte is composed of the following components by mass percentage: 0.3% to 0.6% of N-alkyl indoline additives, 0.2% to 0.5% of fumed silica, 0.3% to 0.5% of anhydrous sodium sulfate, 35% to 38% of sulfuric acid, and the rest is deionized water, and the sum of the mass percentages of the components is 100%; The N-alkyl indoline additive is any one of an N-alkyl isoindoline derivative and an N-alkyl indoline derivative.
[0037] The positive plate includes a positive grid, on which a positive lead paste is coated, the positive grid is a first lead-calcium-tin-aluminum alloy, and the first lead-calcium-tin-aluminum alloy is composed of the following components by mass percentage: 0.04% to 0.08% calcium, 1.0% to 1.5% tin, 0.008% to 0.016% aluminum, and the rest is lead, and the sum of the mass percentages of the components is 100%; The positive electrode lead paste is composed of the following components by mass percentage: lead powder 82%~83%, polyester staple fiber 0.06%~0.10%, stannous sulfate 0.05%~0.25%, antimony trioxide 0.05%~0.25%, graphite 0.10%~0.30%, sulfuric acid aqueous solution with a density of 1.4g / ml 6.5%~7.5%, and the rest is deionized water. The sum of the mass percentages of each component is 100%.
[0038] Example 3 The battery for the flooded parking air conditioner of the present invention comprises a positive plate, a negative plate, a separator, an electrolyte and a battery tank; The electrolyte is composed of the following components by mass percentage: 0.3% to 0.6% of N-alkyl indoline additives, 0.2% to 0.5% of fumed silica, 0.3% to 0.5% of anhydrous sodium sulfate, 35% to 38% of sulfuric acid, and the rest is deionized water, and the sum of the mass percentages of the components is 100%; The N-alkyl indoline additive is any one of an N-alkyl isoindoline derivative and an N-alkyl indoline derivative.
[0039] The positive plate includes a positive grid, on which a positive lead paste is coated, the positive grid is a first lead-calcium-tin-aluminum alloy, and the first lead-calcium-tin-aluminum alloy is composed of the following components by mass percentage: 0.04% to 0.08% calcium, 1.0% to 1.5% tin, 0.008% to 0.016% aluminum, and the rest is lead, and the sum of the mass percentages of the components is 100%; The positive electrode lead paste is composed of the following components by mass percentage: lead powder 82%~83%, polyester staple fiber 0.06%~0.10%, stannous sulfate 0.05%~0.25%, antimony trioxide 0.05%~0.25%, graphite 0.10%~0.30%, sulfuric acid aqueous solution with a density of 1.4g / ml 6.5%~7.5%, and the rest is deionized water. The sum of the mass percentages of each component is 100%.
[0040] The negative plate includes a negative grid, on which negative lead paste is coated, the negative grid is a second lead-calcium-tin-aluminum alloy, and the second lead-calcium-tin-aluminum alloy is composed of the following components by mass percentage: 0.10% to 0.12% calcium, 0.1% to 0.4% tin, 0.008% to 0.016% aluminum, and the rest is lead, and the sum of the mass percentages of the components is 100%; The negative electrode lead paste is composed of the following components by mass percentage: lead powder 85%~87%, polyester staple fiber 0.06%~0.10%, sodium lignin sulfonate 0.15%~0.25%, ordinary carbon black 0.2%~0.3%, high specific surface area carbon black 0.20%~0.50%, barium sulfate 0.5%~0.7%, vanillin 0.15%~0.25%, sulfuric acid aqueous solution with a density of 1.4g / ml 5.5%~6.5%, and the rest is deionized, and the sum of the mass percentages of each component is 100%.
[0041] Example 4 The invention discloses a storage battery for a flooded parking air conditioner, comprising a positive plate, a negative plate, a separator, an electrolyte and a storage battery tank.
[0042] The electrolyte is composed of the following components by mass percentage: 0.3% to 0.6% of N-alkyl indoline additives, 0.2% to 0.5% of fumed silica, 0.3% to 0.5% of anhydrous sodium sulfate, 35% to 38% of sulfuric acid, and the rest is deionized water, and the sum of the mass percentages of the components is 100%; The N-alkyl indoline additive is any one of an N-alkyl isoindoline derivative and an N-alkyl indoline derivative.
[0043] The positive plate comprises a positive grid, on which a positive lead paste is coated, the positive grid is a first lead-calcium-tin-aluminum alloy, and the first lead-calcium-tin-aluminum alloy is composed of the following components by mass percentage: 0.04% to 0.08% calcium, 1.0% to 1.5% tin, 0.008% to 0.016% aluminum, and the rest is lead, and the sum of the mass percentages of the components is 100%; The positive electrode lead paste is composed of the following components by mass percentage: lead powder 82%~83%, polyester staple fiber 0.06%~0.10%, stannous sulfate 0.05%~0.25%, antimony trioxide 0.05%~0.25%, graphite 0.10%~0.30%, sulfuric acid aqueous solution with a density of 1.4g / ml 6.5%~7.5%, and the rest is deionized water. The sum of the mass percentages of each component is 100%.
[0044] The negative plate includes a negative grid, on which negative lead paste is coated, the negative grid is a second lead-calcium-tin-aluminum alloy, and the second lead-calcium-tin-aluminum alloy is composed of the following components by mass percentage: 0.10% to 0.12% calcium, 0.1% to 0.4% tin, 0.008% to 0.016% aluminum, and the rest is lead, and the sum of the mass percentages of the components is 100%; The negative electrode lead paste is composed of the following components by mass percentage: lead powder 85%~87%, polyester staple fiber 0.06%~0.10%, sodium lignin sulfonate 0.15%~0.25%, ordinary carbon black 0.2%~0.3%, high specific surface area carbon black 0.20%~0.50%, barium sulfate 0.5%~0.7%, vanillin 0.15%~0.25%, sulfuric acid aqueous solution with a density of 1.4g / ml 5.5%~6.5%, and the rest is deionized, and the sum of the mass percentages of each component is 100%.
[0045] The specific surface area of ordinary carbon black is 20 / g~30 / g, the specific surface area of high specific surface area carbon black is 120 / g~180 / g.
[0046] Lead powder is made of electrolytic lead, and is composed of the following components by mass percentage: PbO is 70%~80%, Bi is 0.0002%~0.0006%, Fe is 0.002%~0.005%, Ag is 0.0002%~0.0005%, and the rest is Pb, and the sum of the mass percentages of each component is 100%.
[0047] The chemical formula of N-alkyl isoindoline derivatives is:
[0048] in: Represents hydrogen, ~ alkyl, represent ~ alkyl, Represents hydrogen, ~ alkyl.
[0049] The chemical structural formula of N-alkyl indoline derivatives is as follows:
[0050] in: Represents hydrogen, ~ alkyl, Represents hydrogen, ~ alkyl, represent ~ alkyl.
[0051] Example 5 The battery for the flooded parking air conditioner of the present invention comprises a positive plate, a negative plate, a separator, an electrolyte and a battery tank; The electrolyte is composed of the following components by mass percentage: 0.5% of 1-methyl-2-dodecylisoindoline, 0.3% of fumed silica, 0.5% of anhydrous sodium sulfate, 36%-37% of sulfuric acid, and the rest is deionized water, and the sum of the mass percentages of the components is 100%.
[0052] The positive plate includes a positive grid, on which a positive lead paste is coated. The positive grid is a first lead-calcium-tin-aluminum alloy, which is composed of the following components by mass percentage: 0.04% to 0.08% calcium, 1.0% to 1.5% tin, 0.008% to 0.016% aluminum, and the rest is lead, and the sum of the mass percentages of the components is 100%; The positive electrode lead paste is composed of the following components by mass percentage: 82.5% lead powder, 0.07% polyester staple fiber, 0.15% stannous sulfate, 0.10% antimony trioxide, 0.15% graphite, 6.5% to 7.5% sulfuric acid aqueous solution with a density of 1.4g / ml, and the rest is deionized water. The sum of the mass percentages of the components is 100%; The negative plate includes a negative grid, on which negative lead paste is coated, the negative grid is a second lead-calcium-tin-aluminum alloy, and the second lead-calcium-tin-aluminum alloy is composed of the following components by mass percentage: 0.10% to 0.12% calcium, 0.1% to 0.4% tin, 0.008% to 0.016% aluminum, and the rest is lead, and the sum of the mass percentages of the components is 100%; The negative electrode lead paste is composed of the following components by mass percentage: lead powder 85%, polyester staple fiber 0.06%, sodium lignin sulfonate 0.15%, ordinary carbon black 0.2%, high specific surface area carbon black 0.50%, barium sulfate 0.6%, vanillin 0.20%, sulfuric acid aqueous solution with a density of 1.4g / ml 6.5%, and the rest is deionized, and the sum of the mass percentages of each component is 100%; The specific surface area of ordinary carbon black is 30 / g, the specific surface area of high specific surface area carbon black is 120 / g~180 / g.
[0053] The lead powder is composed of the following components by mass percentage: PbO is 70% to 80%, Bi is 0.0002% to 0.0006%, Fe is 0.002% to 0.005%, Ag is 0.0002% to 0.0005%, and the rest is Pb, and the sum of the mass percentages of the components is 100%; The chemical structure of 1-methyl-2-dodecylisoindoline is as follows:
[0054] The present invention discloses a method for manufacturing a battery for a flooded parking air conditioner, and a specific embodiment thereof is as follows: Example 6 According to the components and their contents selected in the above-mentioned embodiment 5, a battery for a flooded parking air conditioner is manufactured, and the specific steps are as follows: Step 1, preparing electrolyte for forming a battery for a flooded parking air conditioner; Step 1.1, weigh the following by mass percentage: 0.5% 1-methyl-2-dodecylisoindoline, 0.3% fumed silica, 0.5% anhydrous sodium sulfate, 36%-37% sulfuric acid, and the rest deionized water, the sum of the mass percentages of the components being 100%; Step 1.2, firstly prepare a sulfuric acid aqueous solution by mixing the sulfuric acid and deionized water weighed in step 1.1; then add the 1-methyl-2-dodecylisoindoline, fumed silica, and anhydrous sodium sulfate weighed in step 1.1 into the sulfuric acid aqueous solution, and continuously disperse for 15 minutes using a stirrer with a rotation speed of 2700 to 3100 rpm to obtain a sulfuric acid dispersion; Step 1.3: Add deionized water to the sulfuric acid dispersion obtained in step 1.2. The mass percentage of is adjusted to 26.0% to 29.0% to obtain a battery formation electrolyte for a flooded parking air conditioner; Step 2: inject the electrolyte of step 1 into the battery assembled with positive plate, negative plate, separator and battery tank, and use staged constant current formation for 23h to 27h. The mass percentage reaches 35.0%~38.0%, and a flooded parking air conditioner battery is obtained.
[0055] Comparative Example 1 A constant capacity discharge cycle test was performed. The flooded parking air conditioner battery obtained in Example 6 was placed in a water bath at a temperature of 23°C to 27°C. Before the test, the flooded parking air conditioner battery was charged at a constant voltage of 16.0V and a current limit of 55A for 24 hours, and then tested. The specific steps are as follows: Step 1: Discharge at 30A for 30min; Step 2: Discharge at 16A for 5h30min; Step 3: Charge at a constant voltage of 14.0V and a current limit of 70A for 8 hours; Step 4: Continuously cycle the operations of steps 1-3. When the voltage of the battery during the discharge process is lower than 10.0V, the test is terminated. The number of completed cycle units is counted, which is the constant capacity discharge cycle capacity of the battery for the flooded parking air conditioner of the present invention. The test results are compared with the constant capacity discharge cycle capacity test results of conventional batteries. Figure 1 As shown, after 75 constant capacity discharge cycles of the conventional battery, the terminal voltage of the battery is lower than 10.0V; while the constant capacity discharge cycle capacity of the flooded parking air conditioner battery of the present invention reaches 510 times; The specific calculation of constant capacity discharge depth is as follows: The discharge capacity of the constant capacity cycle is: 30×0.5+16×5.5=103Ah; Rated capacity of battery: 220Ah; Constant capacity discharge depth: 103÷220=46.8%.
[0056] Comparative Example 2 A full-capacity discharge cycle test was conducted. The flooded parking air conditioner battery obtained in Example 6 was placed in a water bath at a temperature of 23°C to 27°C. Before the test, the flooded parking air conditioner battery was charged at a constant voltage of 16.0V and a current limit of 55A for 24 hours, and then tested. The specific steps are as follows: Step 1: Discharge continuously with a current of 40A until the voltage reaches 11.1V and the discharge ends. Record the discharge time. Step 2: Charge continuously for 6.0 hours with a single cell average voltage of 14.0V and a current limit of 70A; Step 3: Discharge continuously for 20 minutes with a current of 40A; Step 4: Charge for 1.5 hours with a single cell average voltage of 14.0V and a current limit of 70A; Step 5: Discharge continuously for 20 minutes with a current of 40A; Step 6: Charge for 2 hours with a single cell average voltage of 14.0V and a current limit of 70A; Step 7: Charge continuously for 4 minutes with a current of 50A; Step 8: Discharge continuously with a current of 40A until the average voltage of a single cell reaches 11.1V, and then the discharge is terminated and the discharge time is recorded; Step 9, loop through steps 2 to 8; Step 10: When the discharge in step 3 or step 5 is completed and the voltage of the battery for the flooded parking air conditioner is lower than 11.1V, or the discharge time in step 8 is lower than 40% of the discharge time measured in step 1, the test is completed; Step 11, counting the number of effective units completed in step 2 to step 8, which is the full-capacity discharge cycle endurance of the battery for the flooded parking air conditioner of the present invention, and comparing the test results with the full-capacity discharge cycle endurance test results of conventional batteries, as shown in the following example: Figure 2 As shown, after 150 full-capacity discharge cycles of the existing conventional battery, the discharge time is less than 40% of the first discharge time; while after 250 full-capacity discharge cycles of the flooded parking air conditioner battery of the present invention, the discharge time is still more than 80% of the first discharge time. At the same time, the 40A discharge ends at 11.1V, so that all the electricity stored in the battery is discharged, that is, 100% discharge depth (DOD) cycle. Through the above verification examples 1 and 2, it can be clearly seen that the constant capacity discharge cycle capacity and full capacity discharge cycle endurance of the flooded parking air conditioner battery of the present invention are better than those of the existing conventional batteries. The battery for flooded parking air conditioners has large capacity and starting capacity, and has long deep cycle endurance and service life. The full capacity discharge depth reaches 100%, which can obviously meet the requirement that the battery discharge depth is more than 50%.
Claims
1. A battery for a flooded parking air conditioner, characterized in that: It includes positive plates, negative plates, separators, electrolytes and battery tanks; The electrolyte is composed of the following components by mass percentage: 0.3% to 0.6% of N-alkyl indoline additives, 0.2% to 0.5% of fumed silica, 0.3% to 0.5% of anhydrous sodium sulfate, 35% to 38% of sulfuric acid, and the rest is deionized water, and the sum of the mass percentages of the components is 100%; The N-alkyl indoline additive is any one of an N-alkyl isoindoline derivative and an N-alkyl indoline derivative.
2. The flooded parking air conditioner battery according to claim 1, characterized in that: The positive plate comprises a positive grid, on which a positive lead paste is coated, the positive grid is a first lead-calcium-tin-aluminum alloy, and the first lead-calcium-tin-aluminum alloy is composed of the following components by mass percentage: 0.04% to 0.08% calcium, 1.0% to 1.5% tin, 0.008% to 0.016% aluminum, and the rest is lead, and the sum of the mass percentages of the components is 100%; The positive electrode lead paste is composed of the following components by mass percentage: 82%-83% lead powder, 0.06%-0.10% polyester staple fiber, 0.05%-0.25% stannous sulfate, 0.05%-0.25% antimony trioxide, 0.10%-0.30% graphite, 6.5%-7.5% sulfuric acid aqueous solution with a density of 1.4g / ml, and the rest is deionized water, and the sum of the mass percentages of the various components is 100%.
3. The flooded parking air conditioner battery according to claim 1, characterized in that: The negative plate comprises a negative grid, on which negative lead paste is coated, the negative grid is a second lead-calcium-tin-aluminum alloy, and the second lead-calcium-tin-aluminum alloy is composed of the following components by mass percentage: 0.10% to 0.12% calcium, 0.1% to 0.4% tin, 0.008% to 0.016% aluminum, and the rest is lead, and the sum of the mass percentages of the components is 100%; The negative electrode lead paste is composed of the following components by mass percentage: 85%-87% lead powder, 0.06%-0.10% polyester staple fiber, 0.15%-0.25% sodium lignin sulfonate, 0.2%-0.3% ordinary carbon black, 0.20%-0.50% high specific surface area carbon black, 0.5%-0.7% barium sulfate, 0.15%-0.25% vanillin, 5.5%-6.5% sulfuric acid aqueous solution with a density of 1.4g / ml, and the rest is deionized water, and the sum of the mass percentages of the various components is 100%.
4. The flooded parking air conditioner battery according to claim 3, characterized in that: The specific surface area of the ordinary carbon black is 20 / g~30 / g, the specific surface area of high specific surface area carbon black is 120 / g~180 / g.
5. The flooded parking air conditioner battery according to claim 2 or claim 3, characterized in that: The lead powder is made of electrolytic lead, and is composed of the following components by mass percentage: PbO is 70% to 80%, Bi is 0.0002% to 0.0006%, Fe is 0.002% to 0.005%, Ag is 0.0002% to 0.0005%, and the rest is Pb, and the sum of the mass percentages of the various components is 100%.
6. The flooded parking air conditioner battery according to claim 1, characterized in that: The chemical structural formula of the N-alkyl isoindoline derivative is: in: Represents hydrogen, ~ alkyl, represent ~ alkyl, Represents hydrogen, ~ alkyl.
7. The flooded parking air conditioner battery according to claim 1, characterized in that: The chemical structural formula of the N-alkyl indoline derivative is as follows: in: Represents hydrogen, ~ alkyl, Represents hydrogen, ~ alkyl, represent ~ alkyl.
8. A method for manufacturing a battery for a flooded parking air conditioner, characterized in that: The specific steps are as follows: Step 1, preparing electrolyte for forming a battery for a flooded parking air conditioner; Step 2: Inject the electrolyte used in step 1 into the battery assembled with positive plate, negative plate, separator and battery tank, and use staged constant current formation for 23h to 27h. The mass percentage reaches 35.0%~38.0%.
9. The method for manufacturing a battery for a flooded parking air conditioner according to claim 8, characterized in that: The specific steps of configuring the electrolyte for forming the battery for the flooded parking air conditioner in step 1 are as follows: Step 1.1, weighing by mass percentage: 0.3% to 0.6% of N-alkyl indoline additives, 0.2% to 0.5% of fumed silica, 0.3% to 0.5% of anhydrous sodium sulfate, 35% to 38% of sulfuric acid, and the rest of deionized water, the sum of the mass percentages of each component being 100%; the N-alkyl indoline additive is any one of an N-alkyl isoindoline derivative and an N-alkyl indoline derivative; Step 1.2, firstly prepare a sulfuric acid aqueous solution by using the sulfuric acid and deionized water weighed in step 1.1; then add the N-alkyl indoline additive, fumed silica, and anhydrous sodium sulfate weighed in step 1.1 to the sulfuric acid aqueous solution, and continuously disperse for 15 min to 20 min using a stirrer with a rotation speed of 2700 to 3100 rpm to obtain a sulfuric acid dispersion; Step 1.3: Add deionized water to the sulfuric acid dispersion obtained in step 1.
2. The mass percentage of is adjusted to 26.0% to 29.0% to obtain a battery formation electrolyte for a flooded parking air conditioner.